Module 1. The Basics: Gender Equality - CGIAR Research Program on Forests, Trees and Agroforestry (CGIAR Research Program on Forests, Trees and Agroforestry, 2021)
This guide supports the Gender and Inclusion in Forest Landscape Restoration (FLR) e-learning course. The course aims to build the capacities and understanding of diverse stakeholders on the gender and FLR nexus and address inequalities for more equitable and sustainable FLR.